2020
DOI: 10.1093/carcin/bgaa102
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA is a sensitive marker for routine monitoring of treatment response in advanced colorectal cancer

Abstract: Accurate assessment of chemotherapy response provides the means to terminate ineffective treatment, trial alternative drug regimens or schedules and reduce dose to minimize toxicity. Here, we have compared circulating tumor DNA (ctDNA) with carcinoembryonic antigen (CEA) for the cycle by cycle assessment of chemotherapy response in 30 patients with metastatic colorectal cancer. CtDNA (quantified using individualized ddPCR assays) and CEA levels were determined immediately prior to each chemotherapy cycle over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Early investigations in unresectable mCRC, whereby combination cytotoxic chemotherapy is standard, demonstrated feasibility in serial plasma ctDNA assessments with correlations in changes in ctDNA level with tumor response (by CEA and imaging) to various systemic therapy regimens [ 112 , 113 , 114 , 115 ]. Longitudinal sampling of ctDNA in this population was more sensitive than CEA for radiographic progression events where rises in ctDNA occurred significantly earlier than CEA [ 116 ]. Many groups have shown ctDNA-based genotyping of KRAS to have value for prognosticating survival to combination chemotherapy and predicting early emergence of resistance during chemotherapy with lead times as early as 51 days before radiographic progression [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Prediction Of Response To Systemic and Surgical Therapies In Metastatic Colorectal Cancermentioning
confidence: 99%
“…Early investigations in unresectable mCRC, whereby combination cytotoxic chemotherapy is standard, demonstrated feasibility in serial plasma ctDNA assessments with correlations in changes in ctDNA level with tumor response (by CEA and imaging) to various systemic therapy regimens [ 112 , 113 , 114 , 115 ]. Longitudinal sampling of ctDNA in this population was more sensitive than CEA for radiographic progression events where rises in ctDNA occurred significantly earlier than CEA [ 116 ]. Many groups have shown ctDNA-based genotyping of KRAS to have value for prognosticating survival to combination chemotherapy and predicting early emergence of resistance during chemotherapy with lead times as early as 51 days before radiographic progression [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Prediction Of Response To Systemic and Surgical Therapies In Metastatic Colorectal Cancermentioning
confidence: 99%
“…Several studies have described the use of KRAS mutant ctDNA as a marker of response to chemotherapy and disease progression in pancreatic cancer, with changes in ctDNA during treatment being more rapid and pronounced than changes in proteinbased tumor markers [36,37]. A recent study in metastatic colorectal cancer showed similar results, comparing ctDNA with carcinoembryonic antigen (CEA) for the assessment of chemotherapy response and finding ctDNA to be a more sensitive and responsive marker of tumor burden than CEA [19]. In line with these studies, we observed a correlation between ctDNA levels and response to treatment or progressive disease in the majority of aGCT patients, with chemotherapy leading to a more pronounced decrease in ctDNA as compared to inhibin B.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence, ctDNA harbors tumor-specific genetic alterations [16]. With the detection of these tumor-specific mutations in patients' plasma samples, ctDNA has been investigated as a genomic biomarker for disease monitoring and the assessment of treatment response in many cancer types including nonsmall cell lung cancer, breast cancer, colorectal cancer, gastric cancer, bladder cancer and ovarian cancer [17][18][19][20][21][22]. Techniques used for the detection of ctDNA include polymerase chain reaction (PCR) to identify specific mutations in single genes, and targeted next-generation sequencing (NGS) to assess alterations in multiple genes at once.…”
Section: Introductionmentioning
confidence: 99%
“…This technique of deep sequencing, using molecular barcodes to improve accuracy in variant detection, has been used at diagnosis in order to identify actionable genetic alteration with targeted therapies available for treatment or hotspot mutations to be tracked with ddPCR during follow up, with a detection of variant allele frequency down to 1ā€“5% [ 84 , 85 ]. Further investigations are needed to find the real limit of detection of this technology, which may be below 1% as other techniques using molecular barcoding.…”
Section: Detection Of Ctdna By Sequencing Technologiesmentioning
confidence: 99%